Enforcing Ecological Borders between the Human and the Nonhuman: Adapting Pygmalion’s Benevolent Galatea into Frankenstein’s and Contemporary Monsters - Robert Geal (Interfaces)
Humans are evolutionary adaptations of other biological organisms. However, socio-cultural adaptations associated with the Neolithic Agricultural Revolution, the rise of monotheism, and the Scientific Revolution, have contributed to a radical ontological separation of the human from the nonhuman. This false binary opposition facilitates humanity’s destructive behaviour towards nonhuman components of our biosphere, threatening the existence of our species. This article explores the historical development of artistic texts that demonstrate anxieties about transgressing borders between the human and the nonhuman. These texts use repeated narrative and thematic topoi that are adapted to reflect historical attitudes towards human/nonhuman borders. Palaeolithic culture produced art which demonstrated a lack of borders between the human and the nonhuman, but following the Agricultural Revolution, ecophobic cultures produced fictional narratives warning about the monstrous consequences of transgressing human/nonhuman borders. The article traces these ecophobic borders from the polytheistic ‘Pygmalion’ narrative, through the monotheistic/scientific Frankenstein narrative, to contemporary films about human/nonhuman borders such as The Terminator and Toy Story.